Farmyard Beat - Craig, Lindsey (New York : Random House Childrens Books, 2012)
The sounds of the farm animals create a lively beat that keep Farmer Sue, the chicks, sheep, and other farm animals awake.
On board pages.
new kids book 2023 fall.
Accelerated Reader AR
Keywords: Domestic animals -- Juvenile fiction; Bedtime -- Juvenile fiction; Stories in rhyme; Board books; Fiction